The Urgency of Implementing a Cyber Notary in Indonesia: A Comparative Study with The United States - Tan, Winsherly; Agustini, Shenti; Situmeang, Ampuan (SASI, 2024)
Introduction: Current technological developments have an influence on all aspects of human life, including government administration. Notaries are non-governmental public officials who provide public services in providing good governance for the community. However, notarial services in Indonesia are carried out conventionally, which slows down notarial services. Different things happened in America. America is a country that has advanced technology.Purposes of the Research: The aim of this research is to analyze the urgency of implementing cyber notary in Indonesia, find differences in legal regulations and application of law regarding cyber notary in Indonesia and America and find the right solution in organizing cyber notary in Indonesia.Methods of the Research: The research used normative juridical method with secondary data from primary legal sources including various laws and acts like Law Number 2 of 2014, Law Number 30 of 2014, and others related to notarial acts, personal data protection, and blockchain technology in California and Illinois.Results of the Research: The research reveals Indonesia lacks comprehensive laws for cyber notaries. Learning from the US, which has established regulations, Indonesia needs to revise its Notary Law to incorporate cyber notaries and uphold principles of good governance.